Synthesis of MoS2/graphene nanocomposite by facile ultrasonic-assisted hydrothermalmethod - Le Ngoc, Long; Pham Trung, Kien; Tran Van, Khai (Vietnam Journal of Science and Technology, 2019)
In this report, thin layers of MoS2 were in-situ incorporated into graphene oxide (GO) to form MoS2/graphene nanocomposite by a facile ultrasonic-assisted hydrothermal method. X-ray Diffraction (XRD) and Raman analysis revealed that the as-synthesized MoS2 nanosheets crystalized in hexagonal phase 2H-MoS2 while High Resolution Transmission Electron Microscopy (HRTEM) images confirmed that MoS2 layers with average thickness of ~5–6 nm (6–8 layers) attached on the edges and surfaces of graphene sheets with high density and uniform shape restacking in three-dimensional (3D) architectures. The Scanning Transmission Electron Microscopy – Energy Dispersive X-ray spectrum (STEM-EDX) investigation further confirmed the low impurity of MoS2/graphene composite, and the well repairing of defects in GO surfaces during the hydrothermal process. Our approach is promising for a scalable, inexpensive, and accurate strategy to fabricate state-of-the-art materials with a certain structure for various practical applications such as electrode material for Lithium battery or supercapacitor.